1992
DOI: 10.1128/aac.36.3.647
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive assay for fluconazole which uses gas chromatography with electron capture detection

Abstract: Fluconazole, an orally active antifungal agent, has been shown to be clinically beneficial for maintenance therapy of cryptococcal meningitis. A sensitive gas-liquid chromatographic assay with electron capture detection, which required only a single extraction step and precluded any pretreatment of the chromatographic column, was developed for fluconazole. The assay was linear from 0.1 to 20 p,g/ml, with a correlation coefficient of 0.999. The intraassay and interassay coefficients of variation were less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This can be summarized as the following: The literature survey reveals several analytical methods used for quantitative determination of FLZ in body fluids and pharmaceutical preparations. These methods include high-performance liquid chromatography [2][3][4][5][6][7][8] , liquid chromatography-tandem mass spectrometry [9][10][11] , gas chromatography [12][13][14][15] ,micellar electrokinetic capillary chromatography 16 and bioassay 17 .…”
Section: Theory Of Ratio Difference Spectrophotometric Methods (Rdsm)mentioning
confidence: 99%
“…This can be summarized as the following: The literature survey reveals several analytical methods used for quantitative determination of FLZ in body fluids and pharmaceutical preparations. These methods include high-performance liquid chromatography [2][3][4][5][6][7][8] , liquid chromatography-tandem mass spectrometry [9][10][11] , gas chromatography [12][13][14][15] ,micellar electrokinetic capillary chromatography 16 and bioassay 17 .…”
Section: Theory Of Ratio Difference Spectrophotometric Methods (Rdsm)mentioning
confidence: 99%
“…There are various analytical studies reported in literature for the determination of fluconazole in biological fluids by GC [1][2][3][4][5][6] GC-MS, [7] HPLC, [8][9][10][11][12][13][14][15][16][17][18] SFC [19] and by microbiological bioassays. There are various analytical studies reported in literature for the determination of fluconazole in biological fluids by GC [1][2][3][4][5][6] GC-MS, [7] HPLC, [8][9][10][11][12][13][14][15][16][17][18] SFC [19] and by microbiological bioassays.…”
Section: Introductionmentioning
confidence: 99%
“…This potentially exposes individuals to organic solvents or requires additional washing time to clean the pump and column as a result of the use of buffers. Gas chromatography/mass spectrometry, liquid chromatography/mass spectrometry methods that are available are sen sitive, but the sample preparation is sometimes laborious [7][8][9][10]. There is no simple, specific, sensitive, and reproducible analytical method available to quantify FLA in human plasma.…”
Section: Introduction ▼mentioning
confidence: 99%